Pelacakan Gen Sitokrom Oksidase Sub Unit I (COI) DNA Mitokondria Itik Tegal (Anas domesticus) Menggunakan Primer Universal - Wibowo, Sarwo Edi; Djaelani, Muhammad Anwar; Kusumaningrum, Hermin Pancasakti (Bioma : Berkala Ilmiah Biologi, 2013)
Currently local ducks are generally quite difficult to find in a big farm in Inonesia, including Tegal ducks. Tegal ducks is one of the genetic resources native to Indonesia with it’s advantages in terms of high and large egg production. Conservation and development of local ducks have strived to maintain our existence of Indonesian livestock germplasm. If such information is not superior to native species exist, the opportunity to increase his lead further also getting smaller. Tracking the mitochondrial COI gene DNA of Tegal ducks may underlie the process of an organism's genetic characterization. Information about Tegal duck mitochondrial DNA has not been done. The information obtained can be used for optimization of duck products native to Indonesia both in physiological aspects, phylogeny and genetic engineering. The research method used in this research is tracking COI gene data from Gen Bank with the programs Clustal X and Genedoc. Tracking then continued using universal primers HCO and LCO. The results of the data followed up with the isolation and amplification of COI gene mitochondrial DNA as well as the optimization of PCR conditions. The results showed mitochondrial DNA COI gene Tegal ducks were amplified with primer LCO obtain DNA fragments of length less than 250 bp. Kata kunci: duck’s from Tegal, COI gene, mitochondrial DNA